Knowledge, attitude and practice of prescribing antibiotics among dental practitioners in Chitwan - Paudel, Gita; Shah, Arun Kumar; Palikhey, Anjan; Khanal, Nikita; Karki, Sirisa; Chaurasia, Lokeshwar; Chaulagain, Rajib (Europasian Journal of Medical Sciences, 2021)
Background: Antibiotic resistance in recent years has become a major threat to public health globally. In dental practice, antibiotics and analgesics are commonly used for infection control and management of pain. The knowledge, attitude and practice skills of antibiotic prescription by dental practitioners should be continuously evaluated. The aim of this study was to assess the knowledge, attitude and practice regarding antibiotic prescription among dental practitioners. Methods: A descriptive cross-sectional study was carried out to determine the knowledge, attitude and practice regarding antibiotic prescription among dental practitioners. A self-administered questionnaire was used to collect information which was adopted from previous studies. A briefing was given to the participants about the nature of the study and the procedure of completing the questionnaire was explained. After completion of the questionnaire, data was collected, reviewed, organized and expressed as counts/percentages and statically analyzed using SPSS version 16. Result: The current study showed that majority of the participants had average knowledge (52.7%) regarding antibiotic resistance but despite of that they have been prescribing antibiotic without proper guidelines. In this study, Amoxicillin (69.1%) followed by amoxicillin-clavulanic acid (25.5%) combination were the most commonly prescribed drugs used for the management of oral infections, but were prescribed based on symptoms without taking care of guidelines. Conclusion: Dental practitioners had knowledge of antibiotic prescription and its resistance however they have been prescribing antibiotic without proper guidelines. It is deemed necessary to update the knowledge and enhance the careful use of antibiotics.